Silesians in Texas and Upper Silesia: anthropometric, functional and physical activity characteristics - Rożek-Piechura, Krystyna; Ignasiak, Zofia; Kurzaj, Monika; Sławinska, Teresa; Skrzek, Anna; Kozieł, Sławomir; Malina, Robert M. (Anthropological Review, 2020)
Anthropometric, functional and physical activity characteristics of contemporary adult descendants of Upper Silesian immigrants to Texas in the mid-19th century and current residents in Upper Silesia were compared. The sample included 45 residents in Central Texas, 25 women and 20 men, and 36 residents in rural Upper Silesia, 24 women and 12 men, 54-76 years of age. Variables included selected demographic characteristics, anthropometry, estimated body composition, several physiological indicators, strength and functional fitness, and physical activity. Sex-specific MANCOVA and Chi square were used for comparisons. Descendants of Silesian immigrants to Texas were taller, on average, while differences in other anthropometric variables were variable. All residents in Silesia and the majority of descendants of Silesian migrants to Texas were overweight or obese. Differences in hemodynamic and respiratory functions and responses to a 6-minute walk were inconsistent, while none of the fitness variables differed significantly between the samples. Although residents in Upper Silesia were significantly more physically active descendants of Silesians in Texas, >80% of the men and women in both samples scored below the criterion-reference standard for the maintenance of physical independence in the 6-minute walk.